2018
DOI: 10.1002/cbin.11025
|View full text |Cite
|
Sign up to set email alerts
|

Aggravated intestinal apoptosis by ClC‐3 deletion is lethal to mice endotoxemia

Abstract: Our previous study found that ClC-3 chloride channel functioned differently in the vascular and intestinal inflammation, the loss of ClC-3 reduced vascular inflammation but exacerbated intestinal inflammation. To furtherly clarify the role of ClC-3 chloride channels in systemic inflammation, we used LPS-induced endotoxemia model to investigate the response of wild-type and ClC-3 knockout mice to systemic inflammation. The results showed that in the LPS-induced endotoxemia model, the mortality of mice with ClC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…ClC-3 is considered a Cl − /H + exchanger in intracellular vesicles and a chloride channels in the cell membrane [ 15 , 25 ]. Our previous study demonstrated that ClC-3 contributes to the Cl − currents induced by extracellular acidification or estrogen [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ClC-3 is considered a Cl − /H + exchanger in intracellular vesicles and a chloride channels in the cell membrane [ 15 , 25 ]. Our previous study demonstrated that ClC-3 contributes to the Cl − currents induced by extracellular acidification or estrogen [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 92 Studies on other tissues or cells in the intestines and blood vessels have found similar ClC family proteins involved in the process of caspase family-induced apoptosis. 93 …”
Section: Inflammatory Factors Apoptosis and Pyroptosis In Oamentioning
confidence: 99%
“…42,72 Moreover, transfection with ClC-3 siRNA decreased the secretion of LPS, IL, AngII, AT1, TNF-a, and TGF-b1, which can induce the transcription of VCAM1, MCP1, and IAM1. 68,73 In addition, ClC-3-mediated RVD contributes to cellular morphological changes, which allow monocytes to squeeze through pores present on the VEC layer. 74 These findings suggest that ClC-3 may be involved in atherogenesis by promoting monocyte aggregation in the arterial intima.…”
Section: Clc-3 and Macrophage Pro-inflammatory Activationmentioning
confidence: 99%